ChemInform Abstract: Designer Coordination Polymers: Dimensional Crossover Architectures and Proton Conduction. Issue 41 (19th September 2013) - Yamada, Teppei; Otsubo, Kazuya; Makiura, Rie; Kitagawa, Hiroshi
Abstract Review: 78 refs.